2021
DOI: 10.3390/ani11113021
|View full text |Cite
|
Sign up to set email alerts
|

Genetics Responses to Hypoxia and Reoxygenation Stress in Larimichthys crocea Revealed via Transcriptome Analysis and Weighted Gene Co-Expression Network

Abstract: The large yellow croaker (Larimichthys crocea) is an important marine economic fish in China; however, its intolerance to hypoxia causes widespread mortality. To understand the molecular mechanisms underlying hypoxia tolerance in L. crocea, the transcriptome gene expression profiling of three different tissues (blood, gills, and liver) of L. crocea exposed to hypoxia and reoxygenation stress were performed. In parallel, the gene relationships were investigated based on weighted gene co-expression network analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 87 publications
1
1
0
Order By: Relevance
“…In these multiple procedures, oxygen is a vital element to transfer different lipid or carbohydrate into ATP for the survival and functioning of cells. And this pattern was also found in another WGCNA on hypoxia stress in Larimichthys crocea (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…In these multiple procedures, oxygen is a vital element to transfer different lipid or carbohydrate into ATP for the survival and functioning of cells. And this pattern was also found in another WGCNA on hypoxia stress in Larimichthys crocea (Zhang et al, 2021).…”
Section: Discussionsupporting
confidence: 73%
“…Halting energyintensive genome duplication processes leverages time for macromolecular repair and allows for energy redirection [118]. Recovery from stressors on the other hand is accompanied by sustained repair processes [119], [120]. The ppp5c is a cross-tissue hub gene in our study involved in cell cycle arrest and DNA damage repair [121] shown dysregulated in sh under severe stress [122].…”
Section: Cellular Stress In Oxygen Minimum Zonementioning
confidence: 83%